Academic outreach in Medicine: medical practices in a women’s shelter - Firpe, Esther Emanuele; Sales de Souza, Amanda; Soares de Melo, Amélia; Vaz de Mello Frattari, Ana Laura; Marques Miranda de Albuquerque Maranhão, Carolina; Martins França Rodrigues, Ester; das Graças de Azevedo, Mônica; Mie Takeshita, Isabela (Guará Journal, 2025)
This extension project was carried out by medical students from a university in Belo Horizonte through regular visits to a shelter for women facing situations of abandonment. These situations stemmed from factors such as domestic violence, substance abuse, transphobia, and other degrading conditions. The shelter provides quality infrastructure, daily meals, and recreational activities to support the residents. The aim of this study is to share the students’ experiences during the implementation of the extension project. This is a qualitative study, designed using descriptive and observational methods, based on visit logs and reflective meetings between students and faculty mentors. During the visits, topics were addressed according to the specific needs identified by the shelter residents. This experience enabled a deeper understanding of the essential role of active listening and mental health care for victims of physical, psychological, and financial violence. It also highlights the importance of university extension activities in the professional training of medical students.